Pengembangan Sistem Informasi Penjualan Moringa berbasis Web (Studi Kasus : PT Tobisa Global Indonesia) - Chandra Wira Hadikusuma; Issa Arwani; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT Tobisa Global Indonesia is a company engaged in agriculture where its activities are selling organic plants, namely Moringa. Currently PT Tobisa Global Indonesia wants to improve the quality of its services. However, existing business processes are still running manually, starting from the ordering process to payment. Based on the problems obtained, a solution is provided, namely the development of a web-based Moringa sales information system that is integrated with Midtrans as a payment gateway and RajaOngkir as a shipping gateway to simplify the process of purchasing, payment to delivery. The method implemented in this development uses a waterfall with an MVC architecture and uses the MySql database and the Laravel framework. The tests used on this system are validation, compatibility, and UAT (user acceptance testing). Black box testing is a method used for validation testing to test functional requirements to get a 100% success rate. As for compatibility testing using the SortSite application with compatible results showing that this system can run well on various web browsers. The user acceptance testing used aims to test whether the user's needs have been fulfilled to get a test percentage result of 80%. These results fall into the feasible category which indicates that the Moringa sales information system is in accordance with user needs so that it can provide user satisfaction.